Perancangan Asrama Haji Embarkasi dengan pendekatan Arsitektur Tropis - Herawati, Yuni (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2024)
The majority of Indonesia's population is Muslim. Based on the results of the 2010 Central Statistics Agency census, 87.18% of Indonesia's 237,641,326 population adheres to Islam so that Indonesia is classified as one of the countries with the largest Muslim population in the world. For Muslims the pilgrimage which is carried out in the month of Dzulhijjah is one of the perfect conditions for their faith. The report from the Ministry of Religion (Kemenag) shows that Indonesia's haj quota in 2022 will reach 100,051 people. The theme taken in the design of the Embarkation Hajj Dormitory is Tropical Architecture. Climatic conditions that affect building design such as air temperature, solar radiation, wind, humidity, and rainfall.